Implementation of differentiated learning in arts and culture learning of music art material in class 8b of SMPN 1 Mojosari in the 2024/2025 academic year - NABAWI, M HIZA ALTHOF; Murbiyantoro, Heri (Solah, 2025)
This Study aims to describe theimplementation of process-based differentiatedinstruction in the Arts and Culture subject, focusing onMusic Art for class 8B at SMPN 1 Mojosari in theacademic year 2024/2025. The research employed a qualitative descriptive method, utilizing data collectiontechniques such as observation, interviews, anddocumentation. The findings show that theimplementation of differentiated learning in Arts andCulture education with a focus on music art material in class 8B at SMPN 1 Mojosari for the 2024/2025 academic year is carried out through strategies ofdifferentiation in content, process, and product basedon 4 options of learning activity choices. Supportingfactors included the competence of teachers in Artsand Culture is good, positive response from students, availability of learning resources, and support fromschool policies. The obstacles faced are the limitedallocation of time, the misalignment of studentlearning needs, inadequate and limited classroomconditions, the adjustment of the assessment system, and the diversity of motivation in the learning of Artsand Culture. To overcome these challenges, the schoolprovided professional development, mentoring, andsupportive learning facilities. Differentiated instructionwas proven to enhance student motivation, engagement, and understanding of the subject matter.